Disulfiram-ethanol reaction and disulfiram-like reaction - not fully explained ethanol-drug interactions - Krzysztof Badura; Wojciech Owczarek; Anna Wiktorowska-Owczarek (Polish Pharmaceutical Society, 2023)
Disulfiram-ethanol reaction (DER) and disulfiram-like reaction (DLR) are defined as acute intoxication with acetaldehyde after exposure to ethanol with disulfiram or a specific drug. The reaction is still considered as a problem of modern pharmacotherapy. The name of the reaction comes from a drug called disulfiram. In the 1940s, in United States disulfiram was registered for the treatment of alcoholism. DER is the effect of disulfiram's mechanism of action consisting in inhibition of acetaldehyde dehydrogenase (ALDH), which causes accumulation of acetaldehyde, with accompanying alcohol intolerance and aversion to alcohol consumption. Many commonly used drugs have an ability to interact with ethanol and produce the DLR. The reaction can vary in severity of clinical course and can rarely be fatal. Specific for DER mechanism and symptoms have been observed for drugs such as abacavir, several cephalosporins and procarbazine. Based on clinical symptoms, many active agents such as chloramphenicol, griseofulvin, metronidazole and propranolol were considered as active agents increasing the risk of DLR occurrence. However no increase of acetaldehyde level in blood serum was observed, and the mechanism of interaction was different, often including changes in the level of neurotransmitters within the central nervous system. According to other drugs discussed in the article the mechanism of interaction remains unknown. For these reasons reported interactions of drugs (other than disulfiram) have been referred as DLR. For many drugs the available data is limited to only few clinical cases of acute alcohol intolerance. Furthermore, in these cases the mechanism of interaction has not been studied which limits the conclusions and indicates the need for further research in this area. The description of selected drugs also includes information on the potential risk of disulfiram-like reaction obtained from the Summary of Product Characteristics (SmPC) of drugs registered in Poland.